Aesthetic ceramic art composition (Journal of the College of Basic Education, 2022)
The research is concerned with studying the most important constituent and aesthetic elements of the ceramic composition. This research included four chapters.The first chapter was concerned with the importance, limits and objectives of the research with a definition of the most important terms mentioned in the body of the research.As for the second chapter, it included two sections, the first concerned me with the idea of beauty from the past to the present, and the second concerned the most important aesthetic elements in the formation of ceramic artwork. It contained an explanation of the most important basic components of the ceramic work and its aesthetics. And the relationship of each one to the other to form the ceramic artwork.The third chapter also included the analysis of the research sample selected from the research community.As for the fourth, it included the final outcome that came out as a result of the research. It is the interconnection of the basic constituent elements of material, shape and content with its aesthetic elements such as color, texture, expression, and certainly with some other elements of space, proportionality, consistency, etc. to come out with a final result, which is the beautiful shape of the ceramic work.More about this source textSource text required for additional translation informationSend feedbackSide panels